Prevalence of relative age effect in Russian soccer: The role of chronological age and performance - Bezuglov, E. N.; Nikolaidis, P. T.; Khaitin, V.; Usmanova, E.; Luibushkina, A.; Repetiuk, A.; Waskiewicz, Z.; Gerasimuk, D.; Rosemann, T.; Knechtle, B. (International Journal of Environmental Research and Public Health, 2019)
The relative age effect (RAE) has been well studied in adolescent and adult soccer players; however, less information has been available about children engaged in regular soccer training and the role of performance. Thus, the aim of the present study was to examine the prevalence of RAE in children and adolescent soccer players, as well as the role of age and performance. Russian soccer players (n = 10,446) of various ages, playing positions and performance levels were examined for their date of birth. It was observed that RAE was widespread in Russian soccer teams of all age groups. RAE was most pronounced in children teams of the top tier Russian soccer academies and junior Russia national teams, where the proportions of soccer players born in the first quarter were 43.9% and 39.8%, respectively, whereas those born in the fourth quarter of the year were 7.7% and 6.3%, respectively. In top tier soccer academies, RAE did not vary by age group. In the middle tier soccer academies, RAE was less pronounced. It was still prevalent in the junior teams of the top tier clubs of the Russian Premier League, where 14.3% of the soccer players were born in the fourth quarter of the year compared to 42.9% born in the first quarter of the year. RAE can be observed in the top tier Russian adult teams as well, although it is less pronounced there. In summary, RAE is highly prevalent in Russian children and junior soccer and is associated with the level of competitiveness. At the same time, the proportion of players born in the fourth quarter of the year is higher in adult teams than in junior and youth teams, which is most likely due to the wider selection of players, not limited by their age and place of residence. In junior teams, RAE results in a bias towards selection of players who are more physically mature, whereas children who may be more talented but are less developed due to their younger chronological age tend to be overlooked.